2006
DOI: 10.4049/jimmunol.177.4.2304
|View full text |Cite
|
Sign up to set email alerts
|

TRAIL-Mediated Apoptosis in HIV-1-Infected Macrophages Is Dependent on the Inhibition of Akt-1 Phosphorylation

Abstract: HIV-1 uses mononuclear phagocytes (monocytes, tissue macrophages, and dendritic cells) as a vehicle for its own dissemination and as a reservoir for continuous viral replication. The mechanism by which the host immune system clears HIV-1-infected macrophages is not understood. TRAIL may play a role in this process. TRAIL is expressed on the cell membrane of peripheral immune cells and can be cleaved into a soluble, secreted form. The plasma level of TRAIL is increased in HIV-1-infected patients, particularly t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 68 publications
1
33
0
1
Order By: Relevance
“…However, the well-established functional role of proapoptotic genes identified in this work as contributing to apoptosis lends support to the notion that their increased expression may impact apoptosis. Also, while we focused on the relationship between apoptosis and apoptosis-related gene families expressed within cells (p53, ISG, and Bcl2), our data do not exclude contributions by added external mechanisms in vivo affecting total monocyte numbers, such as de novo production and turnover described to occur in SIV infection (40,41) or external factors such as soluble TRAIL in viremic serum (35,38) or increased TRAILmediated apoptosis (30,34,37,75).…”
Section: Cd16mentioning
confidence: 99%
“…However, the well-established functional role of proapoptotic genes identified in this work as contributing to apoptosis lends support to the notion that their increased expression may impact apoptosis. Also, while we focused on the relationship between apoptosis and apoptosis-related gene families expressed within cells (p53, ISG, and Bcl2), our data do not exclude contributions by added external mechanisms in vivo affecting total monocyte numbers, such as de novo production and turnover described to occur in SIV infection (40,41) or external factors such as soluble TRAIL in viremic serum (35,38) or increased TRAILmediated apoptosis (30,34,37,75).…”
Section: Cd16mentioning
confidence: 99%
“…However, we and others have shown that monocytic cells from HIV-infected patients and HIV-negative individuals when infected in vitro can undergo apoptosis (4,5). Moreover, MDMs were shown to undergo apoptosis following in vitro infection with HIV, which was mediated by downregulation of Akt-1 and the FOXO3a transcription factor (6,7). It appears that monocytic cells can undergo apoptosis but may escape HIV cytopathic effects as a result of certain factors reducing their sensitivity to apoptosis (8).…”
mentioning
confidence: 99%
“…This level of plasma TRAIL is well within the biologically relevant concentration range for induction of cell death in immune cells (34).…”
Section: Vol 82 2008 Cell Death During Early Hiv-1 Infection 7703mentioning
confidence: 85%
“…Unlike MPs, exosomes express endosomal markers. MPs have immunomodulatory activities and can promote immune cell death; exosomes are also immunologically active, can suppress immune responses (20,34,42,55), and have been reported to have been found at elevated levels in cases of chronic HIV-1 infection (4). If elevations in levels of immunosuppressive molecules, coupled with early CD4 ϩ T-cell death, occur early following HIV-1 transmission, then these events could potentially define a protected time during which HIV-1 is able to replicate while anti-HIV-1 T-or B-cell responses are suppressed.…”
Section: A Critical Event In Human Immunodeficiency Virus Type 1 (Hivmentioning
confidence: 99%
See 1 more Smart Citation